Depressive Symptoms and Associated Factors in Older Rehabilitation Inpatients: A Cross-Sectional Study. (2nd October 2021) - Owari, Go; Kono, Kenichi; Nishida, Yusuke
Abstract: Aims: To determine prevalence of depressive symptoms and their associated factors in geriatric inpatient rehabilitation. Methods: A cross-sectional study was conducted with 118 older adult inpatients ≥ 65 years using the Geriatric Depression Scale to assess depressive symptoms. Results: Average age of participants was 78.9 years old. Depressive symptoms were found in 46.6% of study participants. Multinomial logistic regression analysis was conducted to confirm the association between presence of depressive symptoms and each factor. Malnutrition was significantly associated with depressive symptoms (OR = 0.90, 95% CI: 0.87–0.96, p < 0.001). Similar results were obtained in model 1 (OR = 0.91, 95% CI: 0.87–0.95, p < 0.001) with the addition of age and gender confounders and in model 2 with additional adjustment for underlying disease, Functional Independence Measure (FIM) exercise items, and FIM cognitive items (OR = 0.92, 95% CI: 0.88–0.96, p < 0.001). Conclusions: Prevalence of depressive symptoms is high in geriatric rehabilitation patients and is associated with malnutrition.